Teaching communicative competence in Health Sciences Education: An analysis of medical students' first biopsychosocial interview in a clinical setting - Moller, Natalie (School of Education, 2017)
Objective: Communicative competence is recognised as essential for establishing an effective doctorpatient relationship. A Primary Health Care-led curriculum places this established relationship at the heart of all interactions and interventions between the patient and the health professional. Medical students at the University of Cape Town are taught in the Clinical Skills Department how to communicate and interact with patients in the pre-clinical years of training using primarily role play. This study examines how medical students transform classroom-based teaching into authentic clinical practice that follows Primary Health care principles in order to evaluate the effectiveness of the Clinical Skills strategy for teaching communicative competence. Methodology: Video recordings of three authentic clinical interviews conducted by medical students taking their first comprehensive biopsychosocial interview in a clinical area were analysed. This data was supported by scrutiny of the intended learning outcomes of all pre-clinical courses in which aspects of communication competence was taught as well as teaching observations made of the students within the classroom Conclusion: The study revealed that although the students could structure a biopsychosocial interview the nuances of building a professional relationship with the patient as envisioned in a Primary Health Care-led curriculum proved difficult for them. These findings suggest that using a single pedagogical method in the Clinical Skills department, namely role play, may not be sufficient for teaching medical students how to place the needs of the patient first above their need to learn, diagnose and treat the patient.